Arbitration vs litigation: a study on the effectiveness of arbitration as compared to litigation particularly with regard to the process of settling disputes / Ilyani Noor Khuszairy … [et al.] - Khuszairy, Ilyani Noor; Melor Jasme, Nur Jasreen; Mokhtar, Hanis; Kudang, Lydia (2009)
This research is conducted to study the effectiveness of arbitration as compared to litigation particularly with regard of settling disputes. This research focuses on the procedural law and specifically made comparison between Arbitration Act 2005 and Rules of the High Court 1980. Second Chapter discussed on the development of arbitration in Malaysia. Arbitration is growing as a result of the need for speedier disputes settlement by the citizen. After several amendments were made to achieve the best result, Arbitration Act 2005 was enacted on 30l December 2005. Civil litigation is governed by Court of Judicature Act 1964 and Article 121 of the Federal Constitution. Litigation procedures are much more related with arbitration, but the differences can be seen on the proceedings that are being conducted. In litigation, the procedures are quite rigid and require high degree of formalities and certainties, whereas arbitration requires less rigidity and more flexible. Third Chapter is on the combination of various writings made by several authors, experienced in the arbitration fields. These reviews are important as the sources to find the effectiveness of arbitration. Chapter Four is on the comparison between arbitration and litigation in terms of privacy, formality and several others. This chapter also discuss on the advantages and the limitation of arbitration. The limitation will be remedied by the results of the finding, whereby according to the interview that had been conducted, arbitration was proved as the best alternative disputes resolution as compared to litigation. This was discussed further under Chapter Five.